A reflection on the recent reorganization of the farming uses in Latin America - Segrelles Serrano, José Antonio (Anales de Geografía de la Universidad Complutense, 2008)
The question of property and land distribution has traditionally brought the rural towns of Latin America together in agricultural movements and uprisings of great public significance. However, despite the fact that most South American countries have been experiencing unprecedented agricultural reorganisations for more than fifteen years, the use and distribution of land has rarely been a socio-political topic until now. This reorganisation constitutes a decrease in land destined for food crops and an expansion of the land used for commercial crops, and is necessary due to the complex demand for cereals and meat. Furthermore, many countries in the region have huge external debts and urgently need to export goods in order to be able to pay the interest.
Keywords: Latin America; Agricultural reorganisation; Food crops; Commercial crops